Coello Iza,Mayra Alexandra(2023).EDUCACIÓN AMBIENTAL A ESTUDIANTES DE LA UNIDAD EDUCATIVA “DR. ALFREDO PAREJA DIEZCANSECO” DEL CANTÓN SANTO DOMINGO.Quevedo.UTEQ.70p. - Coello Iza , Mayra Alexandra (2023)
Corn is a crop that requires the use of agrochemicals to control pests, insects, worms, weeds and to improve corn yields, causing damage to the environment and affecting human health due to the inappropriate use of these products. The objective of this work was to evaluate the environmental impacts of the use of agrochemicals in corn production in the canton of Mocache, province of Los Ríos. To identify the agrochemicals, a survey of 331 farmers was conducted, followed by a technical visit to evaluate the environmental impacts caused by agrochemicals on a corn farm, and finally, an environmental management plan was proposed, indicating measures to mitigate the effects caused by these chemicals. The results obtained show that 93.66% use inorganic agrochemicals on their crops, and the agrochemicals most used are gramoxone with 34.44%, radiant or solaris with 67.98%, chlorpyrifos+cypermethrin with 34.74% and urea with 90.63%, and finally the environmental factors most affected by the use of chemical products are the quality of the air, water, soil and human health. Agrochemicals are toxic and harmful to the environment and human health, so they must be used properly to avoid negative effects.